Paralegals in Building Public Legal Awareness: An Efforts to Empower Community Law in the Work Area of the 'Aisyiyah Branch Manager - Anang Dony Irawan; Azizah Nur Hidayat; Yanuar Ramadhana Fadhila; Rubiati; M. Shohibul Ahzam; Sri Bintang Ayu Ningrat (Universitas Muhammadiyah Sidoarjo, 2022)
Paralegals have an important role in providing legal assistance to people who do not have high legal awareness. This research focuses on the efforts of paralegals in building legal awareness and empowering community law in the Work Area of the 'Aisyiyah Branch Manager, Sambikerep District, Surabaya. This research is empirical legal research, namely the application of legal norms in legal practice in society with participatory efforts through the Asset Based Community Development (ABCD) method. The results of research on the role of paralegals in society. The results of the study confirm that the role of paralegals in building community legal awareness in the working area of the head of the 'Aisyiyah branch, Sambikerep District, Surabaya is carried out by paralegal training with the main focus, namely basic knowledge of law and human rights, so as to be able to make solutions and/or strategies in resolving cases cases dealing with the law as well as skills in conducting advocacy related to the application of legal norms. Furthermore, the role of paralegals and efforts to empower community law in the work area of the leadership of the 'Aisyiyah branch, Sambikerep District, Surabaya Participatory orientation to make PCA Sambikerep Members that is oriented as ghost lawyers whose hope is that Sambikerep PCA Members can consciously, actively, and critically fight for their legal rights at the same time can fight for their legal rights through various efforts and available space..